Use of bacterial whole-genome sequencing to understand and improve the management of invasive Staphylococcus aureus infections. Issue 11 (1st November 2016) - Giulieri, Stefano G.; Holmes, Natasha E.; Stinear, Timothy P.; Howden, Benjamin P.
ABSTRACT: Introduction: Management of invasive Staphylococcus aureus infections is complex. Dramatic improvements in bacterial whole genome sequencing (WGS) offer new opportunities for personalising the treatment of S. aureus infections. Areas covered: We address recent achievements in S. aureus genomics, describe genetic determinants of antibiotic resistance and summarise studies that have defined molecular characteristics associated with risk and outcome of S. aureus invasive infections. Potential clinical use of WGS for resistance prediction, infection outcome stratification and management of persistent /relapsing infections is critically discussed. Expert commentary: WGS is not only providing invaluable information to track the emergence and spread of important S. aureus clones, but also allows rapid determination of resistance genotypes in the clinical environment. An evolving opportunity is to infer clinically important outcomes and optimal therapeutic approaches from widely available S. aureus genome data, with the goal of individualizing management of invasive S. aureus infections.